2020
DOI: 10.15408/ijee.v7i1.15541
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of KWL (Know, Want to Know, and Learned) to Improve Students’ Reading Comprehension

Abstract: This study focused on enhancing students’ reading comprehension through the implementation of K-W-L (know, want to know, and learned) strategy at the secondary level. The purpose of K-W-L strategy is to offer construction for stimulating and building students’ schemata, to create a determination of their reading, and to conclude what they acknowledged before. This research applied Classroom Action Research based on the model suggested by Taggart and Kemmis (1998), consisting of five stages: preliminary study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…Based on the result of the study related to the implementation of K-W-L strategy in teaching reading comprehension. This result supported and strengthened the results of previous studies conducted by (Fajri et al, 2019;Made, 2021;Nirwan, 2020;Riswanto et al, 2014;Rusmiati, 2017;Sholeh et al, 2020;Taheri & Mohamadi, 2015;and Wulandari, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on the result of the study related to the implementation of K-W-L strategy in teaching reading comprehension. This result supported and strengthened the results of previous studies conducted by (Fajri et al, 2019;Made, 2021;Nirwan, 2020;Riswanto et al, 2014;Rusmiati, 2017;Sholeh et al, 2020;Taheri & Mohamadi, 2015;and Wulandari, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…There were several studies which investigated regarding the impact of using K-W-L strategy on students' reading comprehension such as Fajri et al (2019) that implementing K-W-L strategy to the tenth-grade students; Made (2021) implementing K-W-L strategy to the tenth-grade students; Nirwan (2020) implementing K-W-L strategy to the English department students in the second semester; Riswanto et al ( 2014) implementing K-W-L strategy to the eighth-grade students; Rusmiati (2017) implementing K-W-L strategy to the eleventh-grade students; Sholeh et al (2020) implementing K-W-L strategy to the eighth-grade students; Taheri & Mohamadi (2015) implementing K-W-L strategy to the first-grade high school students; and Wulandari (2017) implementing K-W-L strategy to the eighth-grade students. The result of these previous studies have showed that the K-W-L strategy could improve students' reading comprehension achievement.…”
mentioning
confidence: 99%
“…Before taking the test, respondents were exposed to the KWL reading method adapted from O'Brien (2007) to guide them through the reading process. This method is proven to activate students' background knowledge, guide their reading as well as organize their thoughts to allow for greater cognition (Sholeh, Rosalina, & Weganova, 2020;Tok, 2013).…”
Section: Data Collectionmentioning
confidence: 99%
“…The teachers may easily adapt this literacy technique to fit the demands of every level of student and every subject area. (Sholeh et al, 2020).…”
Section: (What I Learned)mentioning
confidence: 99%